Generation and Genetic Analysis of Transgenic Maize (Zea Mays L.) Resistant to Herbicide Glyphosate - Yang, Liyan; Sun, Yi (The International Journal of Biotechnology, 2014)
Two new glyphosate-resistant genes from different sources were introduced into a maize hybrid, Hi-II by Agrobacterium-mediated transformation, and the transgenic T0 plants were identified by 2% glyphosate application and PCR detection. Their progeny inheriting stability was determined with Southern-blot hybridization and the transgene segregation ratios were recorded by glyphosate screening.Results showed that the glyphosate-resistant genes were integrated into maize genome which conferred the transgenic plants higher glyphosate tolerence. Transgenic gene in pAX1677 T1 plants followed Mendelian segregation model while it was not the case in pAX1676 T1 plants. Development of T1 plants showed construct pAX1677 excelled to pAX1676.